Optimasi Rute Distribusi Produk PT Indomarco Adi Prima (Stock Point Nganjuk) Dengan Algoritma K-Means Dan Ant Colony Optimization (K-ACO) - Wahyu Bimantara; Bayu Rahayudi; Imam Cholissodin (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Product distribution companies require cost-effectiveness and efficiency, one of the supporting factors a determining the optimal distribution route. The distribution route is closely related to the Traveling Salesman Problem. In the distribution process from the warehouse or stock point, Nganjuk PT Indomarco Adi Prima has a Multiple Traveling Salesman Problem which involves more than one salesman in the distribution process. To solve MTSP problems, you can search for it by traveling to all possible routes. However, when there are more routes, more time is needed. This research is an effort to optimize the distribution route of PT Indomarco Adi Prima's Nganjuk stock point products using the K-Means and Ant Colony Optimization (K-ACO) methods, in which the K-Means method a used to divide MTSP problems into smaller problems than each problem. Then each of these problems will find the shortest route with ACO. In the tests carried out, K-ACO can save salesmen a traveling distance of 565.801 km. While testing using the Silhouette Coefficient, K-Means resulted in a 76.72% better solution when compared to the results of real sales trips. These results indicate that the use of K-ACO can minimize the total distance traveled from the problem.